(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2013)
Study was carried out to check the random behavior of the Karachi Stock Exchange (KSE 100 Index) during the period of past three financial years to know whether investors could generate abnormal profits during the period or otherwise. Tests used were Runs Test, ADF Test, PP Test and Autocorrelation Function Test. During the study it was found that the performance of KSE 100 Index remained in weak form of inefficiency and investors have been able to generate excessive returns on their investment most of the times.